Thermomechanical failure response of notched NiTi coupons. (15th October 2017) - Iliopoulos, A.P.; Steuben, J.C.; Kirk, T.; Baxevanis, T.; Michopoulos, J.G.; Lagoudas, D.C.
Abstract: Emerging applications of shape memory alloys (SMAs) functioning as actuators in areas such as the aeronautic and automotive industries, require better understanding of their failure mechanisms and mechanics under combined thermomechanical loading. In this paper we examine the thermomechanically–assisted fracture of double notched NiTi coupons during thermal cycling sweeps under isobaric loading conditions. This loading path is an idealization of typical loading paths that utilize these alloys as actuators. A new high performance full-field measurement technique known as Direct Strain Imaging is used to produce full-field strain measurements that are of both higher accuracy and higher spatial resolution than previously achievable. Failure by the formation of an unstable crack during cooling is observed in the experiments for bias load levels that are a fraction of the isothermal load needed for failure at the beginning of cooling (at a temperature well above austenite–finish temperature). This is an intriguing response, characteristic of SMAs, that from an energetic point of view is in disagreement with the general view of dissipative processes, such as phase transformation, resulting in fracture toughness enhancement.